2019
DOI: 10.3390/app9020287
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Wastewater Solutions from Anodizing Industry by Membrane Distillation and Membrane Crystallization

Abstract: The treatment of wastewater containing various metal ions is a challenging issue in the anodizing industry. The current study investigates the application of membrane distillation/crystallization (MD/MCr) for the simultaneous recovery of freshwater and sodium sulfate from wastewater originating from a Danish anodizing industry. MD/MCr experiments were performed on supernatant from wastewater obtained after centrifugation. The effect of various feed temperatures and cross-flow velocities on flux and crystal cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…For instance, it was found that commercial membranes could reduce conductivity in the anodising baths significantly [32]. Accordingly, the application of the membrane crystallisation technique to wastewaters discharged from an anodising industry in Denmark provided more than 80% fresh water from the wastewater [33].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it was found that commercial membranes could reduce conductivity in the anodising baths significantly [32]. Accordingly, the application of the membrane crystallisation technique to wastewaters discharged from an anodising industry in Denmark provided more than 80% fresh water from the wastewater [33].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the MD is well suited for the treatment of industrial wastewater [ 18 , 19 ]. Importantly, this technology relies on its capability to treat harmful industrial wastewaters and waste recycling through the recovery of valuable constituents from feed streams [ 20 , 21 , 22 ]. Furthermore, MD is characterized by high permeate quality, simple operation configuration and process conditions, such as temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%